Effect of kinetin on the tiller development in rice - Amer Hamzah, Muazr; Teh, Chui-Yao; Namasivayam, Parameswari; Mohd Yusoff, Nur Fatihah; Ho, Chai-Ling (Springer, 2024)
Tiller development is regulated by genetics, endogenous hormones, and environmental factors. In this study, rice seedlings from four upland and two lowland rice varieties that were treated with 1.0 mg L− 1 kinetin (a synthetic cytokinin) in vitro could produce additional tillers as early as 20 to 30 days after transplanting, compared to the untreated rice seedlings. However, the number of tillers of kinetin-treated upland rice varieties (Bokilong and Gonsulak) grown in greenhouse did not increase although they developed the first tiller 8 to 9 days earlier than the untreated seedlings. In addition, two lowland rice varieties (Kadaria and MR269) grown in upland growth condition produced 73.7% and 46.5% less tillers, respectively, compared to lowland growth condition; possibly due to an increase of abscisic acid and a lower ratio of trans-zeatin to indole acetic acid. Understanding the effects of kinetin to tiller development in rice may help to increase the total number of tillers and yield of upland rice varieties.